2010
DOI: 10.1523/jneurosci.2669-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Motor Area Exerts Proactive and Reactive Control of Arm Movements

Abstract: Adaptive behavior requires the ability to flexibly control actions. This can occur either proactively to anticipate task requirements, or reactively in response to sudden changes. Here we report neuronal activity in the supplementary motor area (SMA) that is correlated with both forms of behavioral control. Single-unit and multiunit activity and intracranial local field potentials (LFPs) were recorded in macaque monkeys during a stop-signal task, which elicits both proactive and reactive behavioral control. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
152
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 66 publications
17
152
1
Order By: Relevance
“…In functional magnetic resonance imaging (fMRI) studies, activation in the right preSMA (and usually also the anterior cingulate) is greater on trials for which participants successfully cancel a prepotent response compared with trials for which they do not (Aron and Poldrack 2006;Aron et al 2007a;Boecker et al 2010;Boehler et al 2010;Cai and Leung 2009;Chevrier et al 2007;Chikazoe et al 2009b;Curtis et al 2005;Hampshire et al 2010;Sharp et al 2010). Neurophysiologic studies have also shown activation in the preSMA prior to and during stopping (Chen et al 2010;Swann et al 2012). Several studies with macroelectrode stimulation in epilepsy patients show that preSMA stimulation leads to the arrest of ongoing vocal or manual movements (Luders et al 1988;Mikuni et al 2006;Swann et al 2012).…”
mentioning
confidence: 99%
“…In functional magnetic resonance imaging (fMRI) studies, activation in the right preSMA (and usually also the anterior cingulate) is greater on trials for which participants successfully cancel a prepotent response compared with trials for which they do not (Aron and Poldrack 2006;Aron et al 2007a;Boecker et al 2010;Boehler et al 2010;Cai and Leung 2009;Chevrier et al 2007;Chikazoe et al 2009b;Curtis et al 2005;Hampshire et al 2010;Sharp et al 2010). Neurophysiologic studies have also shown activation in the preSMA prior to and during stopping (Chen et al 2010;Swann et al 2012). Several studies with macroelectrode stimulation in epilepsy patients show that preSMA stimulation leads to the arrest of ongoing vocal or manual movements (Luders et al 1988;Mikuni et al 2006;Swann et al 2012).…”
mentioning
confidence: 99%
“…Such cue-related response inhibition probably involves multiple executive and motor mechanisms (Duque et al 2010;Stinear et al 2009;Van Der Lubbe et al 2005). Importantly, this inhibitory control relies not only on postcue responsive mechanisms but also on precue proactive mechanisms that depend on the subject's expectations of the trial structure (Jaffard et al 2007Boulinguez et al 2008Boulinguez et al , 2009Boy et al 2010;Chen et al 2010). A major consequence of this is that these proactive mechanisms influence the neutral cue condition, whenever one is set up to measure attentional effects, leading to possible misinterpretations of classical behavioral outcomes ( Fig.…”
mentioning
confidence: 99%
“…The role of pre‐SMA in proactive motor preparation was repeatedly emphasized in research on animals (Fujii, Mushiake, & Tanji, 2002; Halsband, Matsuzaka, & Tanji, 1994) and humans (Chen et al., 2010; Jaffard et al., 2008; Stuphorn & Emeric, 2012; Wardak, 2011). It was especially shown to be causally relevant to the organization of action sequences (Kennerley, Sakai, & Rushworth, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…According to Aron (2011), proactive elements of motor behavior are very prominent in everyday life, even suggesting that the dynamic interaction of proactive and reactive processes underpins almost all real‐life motor actions. Not focusing on the neural correlates of proactive and reactive processes compromises the “ecological validity” of findings (Aron, 2011; Chen, Scangos, & Stuphorn, 2010; Jaffard et al., 2008; Verbruggen, Adams, & Chambers, 2012). Yet, to study such mechanisms in the brain, one requires a robust behavioral paradigm that reliably triggers proactive processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation